Regulation of systemic metabolism by the autonomic nervous system consisting of afferent and efferent innervation. (12th May 2021) - Imai, Junta; Katagiri, Hideki
Abstract: Autonomic nerves, sympathetic and parasympathetic, innervate organs and modulate their functions. It has become evident that afferent and efferent signals of the autonomic nervous system play important roles in regulating systemic metabolism, thereby maintaining homeostasis at the whole-body level. Vagal afferent nerves receive signals, such as nutrients and hormones, from the peripheral organs/tissues including the gastrointestinal tract and adipose tissue then transmit these signals to the hypothalamus, thereby regulating feeding behavior. In addition to roles in controlling appetite, areas in the hypothalamus serve as regulatory centers of both sympathetic and parasympathetic efferent fibers. These efferent innervations regulate the functions of peripheral organs/tissues, such as pancreatic islets, adipose tissues and the liver, which play roles in metabolic regulation. Furthermore, recent evidence has unraveled the metabolic regulatory systems governed by autonomic nerve circuits. In these systems, afferent nerves transmit metabolic information from peripheral organs to the central nervous system (CNS) and the CNS thereby regulates the organ functions through the efferent fibers of autonomic nerves. Thus, the autonomic nervous system regulates the homeostasis of systemic metabolism, and both afferent and efferent fibers play critical roles in its regulation. In addition, several lines of evidence demonstrate the roles of the autonomic nervous system in regulating and dysregulating the immune system. This review introduces variety of neuron-mediated inter-organ cross-talk systems and organizes the current knowledge of autonomic control/coordination of systemic metabolism, focusing especially on a liver–brain–pancreatic β-cell autonomic nerve circuit, as well as highlighting the potential importance of connections with the neuronal and immune systems. Abstract : Metabolic regulation by the autonomic nervous system